The Criminal Justice Activism of Naomi Osaka: A Case Study in the Criminology of Celebrity Culture - Deflem, Mathieu (American journal of criminal justice, 2023)
This paper examines the criminal justice activism of tennis star Naomi Osaka as it evolved during the COVID-19 pandemic regarding matters of police violence and racial justice. Calls to reform and defund the police received much attention in the aftermath of the police killing of George Floyd in May 2020. The Floyd killing also motivated Naomi Osaka to begin her criminal justice activism, which has generally been very well received. Adopting a constructionist perspective, I investigate how Osaka’s criminal justice activism has, in the broader context of the development of celebrity culture, been subjectively motivated and inter-subjectively received by the public and in the news media. Theoretically this paper has the two-fold objective of developing a model of the conditions favorable to the successful reception of celebrity activism and, additionally, of suggesting how such criminologically relevant activism can be understood in terms of a process of celebritization of criminal justice and police reform as causes worthy of attention. This case study of Osaka’s criminal justice activism reveals the important role a celebrity can play in influencing public sentiments about key aspects of policing and crime control as an important element of criminal justice culture.